Photochemistry of Flavonoids. V. Photocyclization of 2-Styryl-4H-chromen-4-ones - HIGUCHI, KYOKO; YOKOE, ICHIRO; KOMATSU, MANKI; SHIRATAKI, YOSHIAKI (Chemical & pharmaceutical bulletin, 1981)
Irradiation of 2-styryl-4H-chromen-4-ones (1) with a high pressure Hg lamp at room temperature under air gave benzo [α] xanthones (2). The cyclization of methoxy-substituted styrylchromones occurred at the para position relative to the OMe group on the styryl ring, whereas 2-[β-(2-naphthyl) vinyl] chromone (3) cyclized at the α-position of the naphthalene ring.